DINAMIKA NAFKAH ISTRI DALAM CERAI GUGAT (Integrasi antara Fikih dengan Konteks Indonesia) - Jarajap, Inawati Mohammad Jainie; Rahmaniah, Amelia; Mulyati, Farihatni (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
ABSTRACT: Support is a wife's right that must be provided by the husband when marriage occurs, even when a divorce occurs, the husband still has several obligations related to support for his wife. However, the reality in Indonesia is that there are dynamics in fulfilling a wife's living in a divorce. That's why this research will describe these dynamics indicates a change in perspective is an integration between fiqh and the Indonesian context that supports strengthening women's rights in Indonesia. This research is a literature study by reviewing a number of fiqh literature and a number of regulations in Indonesia related to the problem under study as well as reviewing existing previous research. The findings in this research show that there has been a dynamic of wives' livelihoods in contested divorces in Indonesia, starting from the absence of clear regulations either in Law Number 1 of 1974 concerning Marriage or the Compilation of Islamic Law to strengthening women's rights which are supported by jurisprudence. as well as the birth of several Supreme Court Circular Letters. Keywords: dynamics, wife's maintenance, divorce lawsuit ABSTRAK: Nafkah merupakan hak istri yang wajib diberikan oleh suami ketika terjadi perkawinan, bahkan ketika terjadi perceraian-pun suami masih mempunyai beberapa kewajiban yang terkait dengan nafkah kepada istrinya. Akan tetapi kenyataan di Indonesia ada dinamika dalam pemenuhan nafkah istri dalam cerai gugat. Karena itulah penelitian ini akan menggambarkan dinamika tersebut yang menunjukkan adanya perubahan cara pandang yang merupakan integrasi antara fikih dengan konteks Indonesia yang mendukung kepada penguatan hak-hak perempuan di Indonesia. Penelitian ini merupakan studi literatur dengan menelaah sejumlah literatur fikih dan sejumlah peraturan-peraturan di Indonesia yang terkait dengan permasalahan yang diteliti serta menelaah penelitian terdahulu yang sudah ada. Temuan dalam penelitian ini menunjukkan bahwa telah terjadi dinamika nafkah istri dalam cerai gugat di Indonesia yang dimulai dari belum adanya pengaturan yang jelas baik dalam Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan ataupun Kompilasi Hukum Islam sampai kepada penguatan hak-hak perempuan yang didukung dengan yurisprudensi serta lahirnya beberapa Surat Edaran Mahkamah Agung. Kata Kunci: dinamika, nafkah istri, cerai gugat